A cidade como imagem e os processos de mediação com os usuários - Balbi, Thiago Machado (2012)
This research has as object the city as image, the question focuses on how that image interferes on the experience of mediation developed with the city users. Through urban visuality, the user/fruitioner of the public space experiences the city considering two basic vectors: one programmed by the public/private powers that uses the city to communicate it as a trade and order the behavior of the users; and another that develops communication processes motivated by the appropriation of the city through the action of the users daily lives. Using the drift as method, proposed by the Situationist International in 1950, and considering that this method consists in the seizure of public space by systematic wanderings, without any concern about a previously planned shift, seeking to rescue the psychogeographical relation between the user and the public space in order to grasp the communicative relations established between the subject and the city transformed into a commodity or assumed/appropriate by this user. In this way, the research will be based on an empirical research which consists on the displacement of the researcher by the city of São Paulo, and the consequent production of a story and imagery cartography in order to find out the possible contradictions arising from the relation between program and project proposed by Giulio Carlo Argan at the essay The crisis of the design (1983) , the risk of programming and the post-historical climate by Vilem Flusser and criticism of the Society of the Spectacle by Guy Debord. The languages and signs seized at the drifts will be analyzed in the light of semiotics of the culture by Yuri Lotman and the indiciary paradigm proposed by the historian Carlo Ginzburg. The theoretical basis of the survey also includes authors and thinkers about the space, cities and urban life, such as Henry Lefebvre, Jane Jacobs, Lucrecia D Alessio Ferrara, Massimo Canevacci, Manuel Delgado and Milton Santos. In addition to other concepts, such as profanation and devices by Giorgio Agamben, smooth and striated spaces by Gilles Deleuze and Felix Guattari, including terms related to them as the nomadic war machine and the apparatus of capture . The study of these relations might reveal how the trial and the control exercised by public/private authorities highlighted in the city s image works and its interference on the users and their daily lives